Economic growth and the environment - Adolfo Figueroa (CEPAL Review, 2013)
The relationship between economic growth and the environment is one of the most significant problems in modern economics. Empirical data are increasingly available, but the theories behind those data remain a matter of debate. This paper presents an elementary theoretical model of the interactions between the economic process and the environment, drawing on a theory developed by Georgescu-Roegen, in which the laws of thermodynamics are applied to the economic process. The model assumes that the growth and distribution process is currently operating amid conditions of environmental distress. The model is able to predict and explain the observed relationship between economic growth and the environment, identifying new public policy implications. The paper thus aims to contribute to the debate on the choices that society must make about the future of humanity.